2016
DOI: 10.4995/raet.2016.3979
|View full text |Cite
|
Sign up to set email alerts
|

Estimación de variables de combustible de copa y de masa, caracterizando el efecto de las claras en su estructura usando LiDAR aerotransportado

Abstract: Forest fires are a major threat in NW Spain. The importance and frequency of these events in the area suggests the need for fuel management programs to reduce the spread and severity of forest fires. Thinning treatments can contribute for fire risk reduction, because they cut off the horizontal continuity of forest fuels. Besides, it is necessary to conduct a fire risk management based on the knowledge of fuel allocation, since fire behaviour and fire spread study is dependent on the spatial factor. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
(58 reference statements)
2
14
1
Order By: Relevance
“…The results obtained for Pinus pinaster forest must be treated with caution, given the very small sample size, although they provide some information about the variables that potentially explain the biomass components. The R 2 values obtained were similar to those obtained by Hevia et al (2016).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results obtained for Pinus pinaster forest must be treated with caution, given the very small sample size, although they provide some information about the variables that potentially explain the biomass components. The R 2 values obtained were similar to those obtained by Hevia et al (2016).…”
Section: Discussionsupporting
confidence: 86%
“…Several studies using either discrete return or full waveform data have demonstrated the LiDAR potential for estimating canopy fuel metrics (González-Olabarria et al 2012;Jakubowksi et al 2013;González-Ferreiro et al 2014;Hermosilla et al 2014;Hevia et al 2016). Typically, discrete systems derive LIDAR metrics related to canopy height and canopy closure, which subsequently are used as independent variables in regression models (Andersen et al 2005;Hall et al 2005;Erdody and Moskal 2010;Skowronski et al 2011;González-Ferreiro et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The first-to-allechoes ratio in our dataset was slightly greater for the lower pulse repetition frequency compared to Naesset (2009), but that could be related to different scanners. CC ALS estimates from ALS point clouds were significantly influenced by commercial thinning, as found in other studies (Ellis et al, 2016;Hevia et al, 2016). In our study, the CC ALS decreased due to thinning by approximately 20% in leaf-on and leaf-off conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Zhao et al (2018) demonstrated a strong correlation between the field-measured and lidar-based forest height growth and biomass increment predictions, and with the availability of high-density ALS data (>7 points per square metre, p m −2 ), change detection at the single-tree level could be realistic, provided with bi-temporal high-density ALS datasets. Hevia et al (2016) carried out thinning experiments with different intensities in four pure and even-aged maritime pine (Pinus pinaster Aiton) stands and found that canopy cover estimates were good indicators for thinning detection. Such reliable methods for mapping of disturbances and forest growth are necessary for national forest stock reporting, but can also enable pre-targeting of forest inventory fieldwork.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, discrete airborne laser scanning (ALS D ) can register larger areas, and it has been widely used to estimate some forest variables at stand-and individual-tree-level by tree segmentation approaches (e.g., [10,11]). Some of them are forest structure variables such as diameter at breast height (DBH) [12,13], basal area [14,15], stem volume [16,17], stem density [13][14][15], stand volume [18,19], fractional cover/gap fraction, and leaf area index (LAI) [20,21]; forest mass variables, such as biomass components [13,17,19]; and forest fuel variables, such as mean and dominant tree heights [18,22], canopy base height, canopy fuel load, and canopy bulk density [19,23]. Moreover, ALS D data have also been used in combination with multispectral or hyperspectral images to classify tree species [24,25] and fuel types [24,26,27].…”
Section: Introductionmentioning
confidence: 99%